Littoral cell angioma of a huge spleen with peripheral blood pancytopenia in a 14-year-old boy: a case report and review of the literature - Gao, Tianyu; Wang, Xingang; Wei, Qiuya; Wang, Chen; Fan, Yong; Wang, Yuebin (Frontiers in Pediatrics, 2024)
Abstract Background: Splenic littoral cell angioma (LCA) is an exceptionally uncommon malignant potential vascular tumor, with infrequent occurrences in pediatric patients. Due to its reliance on histopathological analysis for diagnosis, LCA may be mistakenly identified as other splenic tumors. Patients with LCA may experience anemia or thrombocytopenia, but peripheral blood pancytopenia is infrequent. Case report: A 14-year-old male presented with peripheral blood pancytopenia necessitating hospitalization upon the identification of splenomegaly during physical examination. Following the exclusion of hematological disorders, splenectomy was conducted, confirming LCA through histopathological examination. No metastases or recurrences were observed during the 8-month follow-up. This case represents the first instance of LCA associated with pancytopenia in pediatric patients, to the best of our knowledge. Conclusion: LCA can leads to iron-deficiency anemia or thrombocytopenia, with rare occurrences of pancytopenia, potentially resulting in misdiagnosis as a hematological disorder. Surgical intervention remains an effective treatment for LCA.